Internal and External Banking Determinants on Conventional Banking Profitability in Indonesia - Alisa Fatin Sabreena; Aris Soelistyo; Firdha Aksari Anindyntha (PT. Maju Malaqbi Makkarana, 2026)
This research aims to analyze the influence of internal and external bank factors which include Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Non-Performing Loans (NPL), interest rates, inflation and economic growth on Return on Assets (ROA) in conventional banking in Indonesia. This research uses quantitative methods with a causality approach. The data used is secondary data obtained from bank financial reports and official publications related to the research period. The analysis technique used is panel data regression using model selection tests, classical assumption tests, and hypothesis tests. The research results show that all independent variables simultaneously influence ROA. Partially, NPL has a significant negative effect on ROA, while other variables such as CAR, LDR, interest rates, inflation and economic growth show varying effects on bank profitability. This research concludes that credit risk is the dominant factor influencing banking financial performance.